Peningkatan Kompetensi Digital Lulusan SMK Kabupaten Cirebon Melalui Pelatihan Junior Network Administrator - Yudhistira Arie Wijaya; Edi Tohidi; Alwan Azhar; Andi Ardiansyah (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Junior Network Administrator training for SMK graduates in Cirebon Regency aims to improve skills and competencies in the field of computer networks. The program is designed as a solution to employment challenges by providing competency-based training that refers to industry standards. Training methods include theory, hands-on practice, and case studies relevant to the needs of the world of work. The program evaluation showed an increase in participants' understanding and skills in managing computer networks, configuring network devices, and basic troubleshooting. In addition, participants obtained certifications that can increase their competitiveness in the job market. The training results showed that most of the participants were successful in obtaining jobs or internships in technology companies and related institutions. The success of this program is supported by cooperation between educational institutions, local governments, and the industrial sector. Challenges faced include limited facilities and participants' readiness to deal with rapid technological developments. To improve the effectiveness of the program, it is recommended to improve training facilities, update the curriculum in line with industry developments, and collaborate more closely with the private sector.